Benchmark Ratio of Insurance Penetration (BRIP) as a New Relative Measure of Insurance Development and Benchmarks in Insurance - Pobłocka, Agnieszka (Względna miara rozwoju ubezpieczeń BRIP i benchmarki w ubezpieczeniach, 2024)
Aim: In various fields of science, certain patterns are used to describe and compare phenomena and reference points (benchmarks), e.g.: reference rates (benchmark rates), reference ratios (benchmark ratio), or comparative analyses (the benchmarking) (EY, 2021). In insurance, premium, density and penetration, among others, are used to describe market development. To compare insurance markets, the average is usually used, e.g. average premium, average density or penetration rate. However, the measures used are limited – premium and density do not take into account economic development – or have been ‘devalued’ (penetration rate is often with different premium and GDP growth rates). In effect, a new, more robust paradigm is being sought, i.e. a new insurance growth pattern. Methodology: This paper analyses and evaluates the benchmark ratio of insurance penetration (BRIP) proposed by (Zheng et al., 2008 and 2009) as a new measure of insurance development and examined its advantages and disadvantages. The arithmetic mean was also analysed as a benchmark for comparing different insurance markets. Findings: The BRIP indicator should be used with caution, as it strongly depends on the benchmark used for comparison. If it is adopted at the level of the arithmetic mean for the whole market, the analysis results may be incorrect when the distribution of the examined phenomenon does not have a central tendency. Implications: The results of the study are a new contribution to the evaluation and application of the BRIP indicator in insurance theory. Originality/value: Zheng et al. (2008, 2009) proposed the BRIP indicator as a new benchmark for the development of insurance markets, without knowing that it cannot always be applied. The author of this study fills this gap and shows when this indicator cannot be applied (DeepL-assisted translation).
Financial Sciences. Nauki o Finansach, 2024, vol. 29, no. 1, s. 24-36
Keywords: insurance market; development of the insurance market; benchmark; benchmark ratio of insurance penetration; rynek ubezpieczeń; rozwój rynku ubezpieczeń; względny wskaźnik rozwoju ubezpieczeń; BRIP